2016
DOI: 10.1016/j.radi.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of introducing a skills mix approach to CT head reporting in clinical practice

Abstract: Please cite this publication as follows:Lockwood, P. (2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The majority of studies (n 5 7) focused on advanced radiography practice within the UK healthcare system, while two studies reflected North American practice (USA and Canada). The advanced practice activities considered were radiographer reporting; [32][33][34][35] leading patient review clinics; 36,37 and barium enema examination. 38 Two articles considered the generic attributes of an advanced practice role per se, with a view to service efficiencies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies (n 5 7) focused on advanced radiography practice within the UK healthcare system, while two studies reflected North American practice (USA and Canada). The advanced practice activities considered were radiographer reporting; [32][33][34][35] leading patient review clinics; 36,37 and barium enema examination. 38 Two articles considered the generic attributes of an advanced practice role per se, with a view to service efficiencies.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 The articles were generally considered to be of low-to-moderate quality, evaluating advanced practice activities within a single centre and providing limited robust methodological information required to confirm study quality. With respect to the WHO quality dimensions, 29 six studies considered cost reduction; 32,33,35,[38][39][40] three studies considered reduction in patient morbidity; [32][33][34] two studies considered reduction in time to treatment; 33,34 and two studies considered patient satisfaction. 36,37 No studies considered or reported data relating to time to diagnosis, time to recovery or patient mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The societal cost/benefit to patients from integrating the new intervention could potentially improve reporting services and faster diagnosis. Evidence from studies in XRay 578,589,5960,601,612 CT 623,634 , ultrasound 623 and magnetic resonance imaging 623 support achievable increases in reporting turnaround times. The influence of introducing system efficiencies in reporting enhances patient treatment and management 578,645,656,667 which improves quality of care and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%